Pengaruh Pelaksanaan Penyuluhan Peraturan Perpajakan Terhadap Kepatuhan Wajib Pajak - Dian Kartika Zega; Suzy Noviyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research is a qualitative research that aims to identify the effect of the implementation of tax regulation counseling on taxpayer compliance. Tax is a mandatory contribution to the state that is owed by an individual or entity that is coercive in nature based on the law, with no direct compensation and is used for the purposes of the state for the greatest prosperity of the people. Compliance with taxation is a manifestation of tax regulations in reporting and depositing taxes owed by taxpayers. Socialization is an interaction that is carried out to increase the knowledge of taxpayers and prospective taxpayers related to taxation. This study took 4 (four) resource persons consisting of two Gunungsitoli KP2KP employees and two registered taxpayers. Research data collection was carried out through unstructured interviews by directly visiting sources and asking questions about the information needed by researchers. The results of this study indicate that taxpayer compliance that occurs greatly affects taxpayer knowledge of tax regulations and the quality of tax services provided by KP2KP. Keywords: Taxpayer Compliance, KP2KP, Tax Counseling, Tax Consultation